Preparing of the Future Teachers of Preschool Pedagogics and Psychology to Innovative Professional Activities: Conceptual Approaches - Lyudmyla Kozak (Pedagogical Discourse, 2013)
The basic aspects of conceptual approaches and provisions of future teachers of preschool education and psychology to an innovative professional activity are grounded in the article, it reveals the specific features and innovative professional teacher of preschool pedagogics and psychology, defined a general idea of ​​the concept, presents the goals, objectives, principles, approaches and stages of preparation future teachers of preschool education and psychology to an innovative professional, outlined the content, forms, methods of preparation of future teachers of preschool pedagogics and psychology to an innovative professional and technology of its implementation; highlighted organizational and methodological conditions for training of teachers for innovative professional activities and expected results.